Project Law—A Legal Intermediary between Local and Global Communities: A Case Study from Senegal - Weilenmann, Markus (Anthropologica, 2022)
This article focuses on the working methods of international development agencies. It pays attention to the societal impact of normative orders regulating the conceptualization and implementation of development projects. On the basis of a slum sanitation project in Senegal, it outlines how transnational concepts of rural property relations interfere with local concepts and what kind of reactions a project might set in motion locally, nationally and internationally. Attention will also be paid to the dynamics entailed in the triangular structure of transnational and rural actors and the state and its representatives.